KAJIAN PERENCANAAN PEMBENTUKAN TPA REGIONAL Rencana Daerah Layanan Kota Banjarbaru, Banjarmasin Dan Martapura - Rizki Puteri Mahyudin; Adrias Mashruri; Fathurrazie Shadiq; Yusuf Azis (Universitas Lambung Mangkurat, 2011)
This research is intended to investigate (a) the garbage growth projection, (b) the condition of Final Garbage Destination (FGD) for Banjarbaru, Banjarmasin and Martapura, (c) the planning concept on regional FGD, (d) the landfill model, planning component and technique component priorities on regional FGD for Banjarbaru, Banjarmasin and Martapura. The used method is survey namely deep interview using questionnaire to 14 people that involved in FGD management; and observation. The data analysis covers geometric method, Analytical Hierarchy Process (AHP), Strength Weakness Opportunity Threat (SWOT) and descriptive analysis. The population growth in Banjarbaru (2,4%) is higher than Banjarmasin (1,8%) and Martapura (1,7%). From projection of population growth, the projection of garbage growth can be calculated. Up to 2033, projection of total garbage growth for those cities will be obtained 3.339.762.228 kg that needs about 38,92 ha for FGD land based on the assumption that the project is started from 2014. The Regulation Number 18 Year 2008 about garbage management states that the open dumping is forbidden. Until now, the FGD in those cities still use open dumping because of limited finance, equipment and facilities. Because of the increasing of garbage, it needs a well planned FGD management that is not polluting environment through regional cooperation FGD. SWOT analysis result shows that finance and human resouce quality is the most important thing that should be considered for government in making decision. The result of Analytical Hierarchy Process shows that the selected model landfill is sanitary landfill. The first priority for planning component of FGD is government regulation (decision), and the first priority for technique component is recycling and loading garbage.